Clinical profile of acute drug-induced dystonia in children (Indian Journal of Child Health, 2020)
Background: Acute dystonic reactions are the most common type of extrapyramidal reactions associated with the use of certain drugs. Drug-induced dystonic reactions (DIDRs) are diagnosed based on the detailed history and physical examination. Objective: The objective of the study was to describe the clinical profile, identify the drugs causing dystonic reactions and outcomes in a cohort of children with DIDRs. Materials and Methods: This study is a prospective observational study conducted in patients with DIDRs between February 2019 and January 2020 aged <15 years. DIDRs were diagnosed on the basis of history and physical examination. Results: During the proposed study period, 12 children with DIDRs were identified with a mean age of 50.8 months and eight patients (67%) were boys. The most common cause of DIDRs was with antipsychotics in eight patients (67%) and with antiemetics in four patients (33%). All patients with DIDRs due to antiemetics were infants and received the drug with overdose. These infants needed more diagnostic investigations. Most of the children responded with stoppage of causative drug and administration of benzodiazepine and diphenhydramine. On follow-up, there was no recurrence. Conclusion: DIDRs were common with antiemetics and antipsychotics either with therapeutic dose or overdose. Benzodiazepines and diphenhydramine were more effective drugs in the treatment of DIDRs.